Fuzzy Self-Adaptive Sliding Mode Control for Pneumatic Cylinder Rod-Piston Motion Precision Control. (June 2020) - Iskandar Putra, Mohd; Irawan, Addie; Mohd Taufika, Raja
Abstract: This paper presents the Fuzzy Self-Adaptive Sliding Mode Controller (FSASMC) designed to control a pneumatic cylinder rod-piston motion and precision. The pneumatic system is widely used in the industry due to its advantages such as high weight to power ratio, high traveling speed, clean fluid medium, and cost-effective in terms of price and maintenance. However, due to the high nonlinearity behavior of pneumatic system, the position control of the pneumatic system is still a challenging task. The most critical part of controlling the pneumatic system with various motion is in giving a stable pressure in chambers, while the rod-piston motion is precisely controlled with any shape of inputs with minimum friction. Therefore, FSASMC is proposed to cater to this matter with fast responses through Sliding Mode Control (SMC) and dynamic stability in pressures through Fuzzy Self-adaptive tuning using Fuzzy Logic Control (FLC). The proposed control system is verified, and analysis was emphasized on steady-state error, velocity, pressure in pneumatic cylinder chambers, and frictional force. Simulation results show that the proposed controller approach performing fast-tracking error on pneumatic rod-piston motion with a very low steady-state error, no oscillation and stable in air pressures.